2022
DOI: 10.2478/stattrans-2022-0027
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the effect of new data sources on the consumer price index: a deterministic approach to uncertainty and sensitivity

Abstract: One of the greatest challenges facing official statistics in the 21st century is the use of alternative sources of data about prices (scanned and scraped data) in the analysis of price dynamics, which also involves selecting the appropriate formula of the price index at the elementary group (5-digit) level. When consumer price indices of goods and services are constructed, a number of subjective decisions are made at different stages, e.g. regarding the choice of data sources and types of indices used for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Another method that has been suggested is the use of consumer perception surveys to capture individual differences in perception and preference. Studies have shown that incorporating survey data into CPI calculations can improve the accuracy of CPI measurements and reduce potential bias (Białek et al, 2022). However, this approach is limited by the quality and representativeness of survey data.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Another method that has been suggested is the use of consumer perception surveys to capture individual differences in perception and preference. Studies have shown that incorporating survey data into CPI calculations can improve the accuracy of CPI measurements and reduce potential bias (Białek et al, 2022). However, this approach is limited by the quality and representativeness of survey data.…”
Section: Literature Reviewmentioning
confidence: 99%